Low‐temperature Fischer‐Tropsch synthesis using plasma‐synthesized nanometric Co/C and Fe/C catalysts. (19th June 2016) - Aluha, James; Braidy, Nadi; Dalai, Ajay; Abatzoglou, Nicolas
Abstract: In this study, two analogous nanometric catalysts consisting of carbon‐supported cobalt or iron (Co/C and Fe/C) were synthesized by plasma and tested for Fischer‐Tropsch synthesis (FTS) in a continuously‐stirred tank slurry reactor (CSTSR). Being pyrophoric in nature, these new materials were reduced in situ at 673 K (400 °C) for 24 h using pure H2 gas. The FTS reaction was conducted at 493 K (220 °C), 2000 kPa pressure, and gas hourly space velocity (GHSV) of 3600 mL ·  g c a t − 1 ⋅ h − 1 for 24 h, using a feed stream of 0.6 L/L (60 vol %) H2 and 0.3 L/L (30 vol %) CO, with 0.1 L/L (10 vol %) Ar for mass balance determination. Devoid of promoters and under similar reaction conditions, the Co/C catalyst showed higher CO conversion (42 %) than the Fe/C (25 %), benchmarked against the commercial Fe‐NanoCat ® (32 %). Co/C was more selective toward gasoline production, while Fe/C was more selective toward the diesel fraction. From transmission electron microscopy (TEM) analysis, no significant change in the mean particle size (∼12 nm) was observed in the plasma‐synthesized catalysts before and after FTS reaction, implying that the catalysts did not sinter. Additionally, there were no internal mass transport limitations in these catalysts, making them favourable for FTS. Besides metallic species, X‐ray diffraction (XRD) analysis indicated the presence of carbides in fresh catalysts (Fe3 C in Fe/C and Co3 C in Co/C). Magnetite (Fe3 O4 ) was the most prevalent phase in the used Fe‐NanoCat ® sample, a phase that was below the detection limits of XRD in the used plasma‐synthesized Fe/C sample. Abstract : Structural differences between new catalysts and commercial Fe‐NanoCa.